EFEKTIVITAS LAYANAN PENDAMPINGAN PERUBAHAN BIODATA KARTU KELUARGA DI KANTOR KELURAHAN SEMOLOWARU, KOTA SURABAYA - Angelia Devika Lydia; Sri Wibawani (Jurnal Genta Mulia, 2023)
Changes in biodata on the Family Card are an important administrative process that must be updated with information on the demographic data of family members and marital status. The city of Surabaya as the second largest city in Indonesia has a large population, so there is a need for effective assistance services in the population administration process. This study aims to examine how effective assistance services are in changing Family Card biodata in the city of Surabaya. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research informants are the Head of Village Government and Public Services, Service Sector Officers, community service users. The results of the study show that assistance services for changing family card biodata are generally effective. However, there are still obstacles, such as the lack of knowledge and expertise of employees in serving residents, the lack of outreach activities to the community about the importance of updating population data for family members, the long waiting time to get service, especially when there are technical constraints in the service system that need to be continuously improved so that the process changes to family card biodata went smoothly.